Introduction: Empirical Taxation - Nancy Staudt (Washington University Journal of Law & Policy, 2003)
In this symposium we seek to move beyond theoretical and normative tax policy debates to study the real world effects of taxation. The contributors use a variety of empirical methods to shed new light on a range of complex tax issues. Although the articles in this collection will not settle long-standing debates—some studies raise more questions than they answer—we believe that empirical work is necessary for finding and implementing workable solutions to difficult tax problems. This does not mean we see no role for theorizing in taxation. Just the opposite is true. We hope to subject the best theories to empirical investigation in order to understand better their real-world implications, and ultimately their viability for policy making. Without theory, empiricism is merely a mechanism to describe the existing state of the world; informed by theory, we can use empirical methodologies to assess likely behavioral consequences of legal change can evaluate tax policy over the course of time.
Keywords: Taxation; Social science research; Law -- Study & teaching